Gorgeous gruesome faces - Cheng, Linda (Roaring Brook Press, a division of Holtzbrinck Publishing Holdings Limited Partnership, 2023)
"After a shocking scandal that abruptly ended her teen pop-star career, eighteen-year-old Sunny Lee spends her days longing for her former life and cyberstalking her ex-BFF and groupmate Candie. The two were once inseparable, but that was then -- before all the tragedy and heartache. In the here and now, Sunny is surprised to discover that Candie is attending a new K-pop workshop in Sunny's hometown. Sunny can't resist the chance to join her and finally confront the demons in their past... because she still can't figure out what happened that horrible night when Mina, the third in their tight-knit trio, jumped to her death. Or if the dark and otherworldly secrets Sunny and Candie were keeping had something to do with it... But the workshop brings neither the happy reunion Sunny had hoped for nor answers to her sinister questions. Instead, Sunny finds herself haunted by ghostly visions while her competitors suffer strange injuries, which become even strangers mutilations that soon turn deadly. In her race to survive, Sunny will have to expose just what's behind the carnage -- and whether Candie is out for blood once again -- in Linda Cheng's spellbinding sapphic thriller that will have readers screaming and swooning for more." --